2015
DOI: 10.1007/s00253-015-6863-z
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning recA expression in Staphylococcus aureus for antimicrobial photoinactivation: importance of photo-induced DNA damage in the photoinactivation mechanism

Abstract: Bacterial cell envelope is generally accepted as the primary target for a photo-induced oxidative stress. It is plausible that DNA damage occurs during the antimicrobial photoinactivation. Here we investigate the correlation between DNA damage and photoinactivation by evaluating the level of RecA-based DNA repair system in Staphylococcus aureus. By using exogenous photosensitizers (new methylene blue (NMB), toluidine blue O (TBO), 5,10,15,20-tetrakis(1-methyl-4-pyridinio)porphyrin tetra(p-toluenesulfonate) (TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…The mechanism underlying the bactericidal activity of aBL is unclear. A common hypothesis is that visible aBL excites endogenous photosensitizing compounds that occur naturally within microbial cells, inducing the production of cytotoxic ROS . Within the present work, we made an effort to detect the photosensitizing molecule within P. aeruginosa cells and indicated that PPIX or PPIX‐like derivatives are mainly responsible for the bactericidal effect of aBL.…”
Section: Discussionmentioning
confidence: 82%
“…The mechanism underlying the bactericidal activity of aBL is unclear. A common hypothesis is that visible aBL excites endogenous photosensitizing compounds that occur naturally within microbial cells, inducing the production of cytotoxic ROS . Within the present work, we made an effort to detect the photosensitizing molecule within P. aeruginosa cells and indicated that PPIX or PPIX‐like derivatives are mainly responsible for the bactericidal effect of aBL.…”
Section: Discussionmentioning
confidence: 82%
“…The hypothesis regarding the mechanism of action of aBL was further endorsed by DNA manipulation to knockout the porphyrin synthesis pathway of a microbe sensitive to aBL and then the comparison of the aBL susceptibilities between the knockout mutant and its parental strain (Galbis-Martinez et al, 2012; Grinholc et al, 2015). It was also reported that the endogenous porphyrins patterns in vitro (e.g., porphyrin quantity and porphyrin species) are highly affected by the culturing conditions (e.g., time of culturing, passaging, culture media) (Fyrestam et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Grinholc et al (Grinholc et al, 2015) compared the aBL efficacy towards a wild-type S. aureus reference strain, which is capable of producing endogenous porphyrins, and its isogenic knockout mutant, which lacks the ability to produce endogenous porphyrins due to the knockout of porphyrin biosynthetic pathway. Exposure of the wildtype S. aureus strain to 10 J/cm 2 aBL at 405 nm resulted in >2.5-log 10 CFU reduction.…”
Section: Mechanism Of Action Of Antimicrobial Blue Lightmentioning
confidence: 99%
“… 24 In our previous study examining the S. aureus wild-type reference strain NCTC 8325–4, which is capable of endogenous porphyrin production, and an isogenic knockout mutant (8325–4 Δ hemB ) in which endogenous porphyrin production was blocked, we demonstrated the requirement for endogenous porphyrins for the bactericidal activity of a 405-nm light treatment. 29 …”
Section: Introductionmentioning
confidence: 99%